Vegetable Species in the Palm Grove of The Ouargla Region (Algeria) - Sara Salhi; Souad BABAHANI; Khira Naami; Abdelkader ALLAM (Al-Qadisiyah Journal For Agriculture Sciences, 2022)
The present work on the cultivation of winter vegetable species, which was carried out in the perimeters of development of the six communes of the region of Ouargla. We found that the biodiversity recorded is 16 species and 09 botanical families, during the study period. The most frequent botanical families are : Liliaceae (Allium cepa L.), Chenopodiaceae (Spinacia oleracea.), Asteraceae (Lactuca sativa) and Apiaceae (Daucus carota .). Many local cultivars have been identified; their identification is mainly based on: the origin of the seeds, the shape and color of the fruits. According to the average richness and diversity index calculations, we found that the stations of Sidi Khouiled and Hassi Ben Abdallah have a great diversity, unlike Rouissat and Ouargla where the diversity is low. The local diversity seems to be threatened, this is due to several causes among others the non-reasoned selection of local cultivars and the introduction of hybrid seeds which allows us to validate the first hypothesis that says (the development projects have favored the introduction of many new vegetable species, not traditionally cultivated in the areas and have favored the use of hybrid varieties, with high production potential. This policy induces a genetic erosion, especially for local cultivars) and to reject the second hypothesis that says (the development perimeters participate in the preservation of local cultivars, which ensures their sustainability in the medium and long term).